-4(t-2)+9t=3t-5

Simple and best practice solution for -4(t-2)+9t=3t-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(t-2)+9t=3t-5 equation:


Simplifying
-4(t + -2) + 9t = 3t + -5

Reorder the terms:
-4(-2 + t) + 9t = 3t + -5
(-2 * -4 + t * -4) + 9t = 3t + -5
(8 + -4t) + 9t = 3t + -5

Combine like terms: -4t + 9t = 5t
8 + 5t = 3t + -5

Reorder the terms:
8 + 5t = -5 + 3t

Solving
8 + 5t = -5 + 3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3t' to each side of the equation.
8 + 5t + -3t = -5 + 3t + -3t

Combine like terms: 5t + -3t = 2t
8 + 2t = -5 + 3t + -3t

Combine like terms: 3t + -3t = 0
8 + 2t = -5 + 0
8 + 2t = -5

Add '-8' to each side of the equation.
8 + -8 + 2t = -5 + -8

Combine like terms: 8 + -8 = 0
0 + 2t = -5 + -8
2t = -5 + -8

Combine like terms: -5 + -8 = -13
2t = -13

Divide each side by '2'.
t = -6.5

Simplifying
t = -6.5

See similar equations:

| 0.18(y-9)+0.04y=0.12y-0.03(40) | | C=30(3.14) | | (4x+3)(2x-6)= | | 4t^2-40t+25=0 | | 3y=x^2+7 | | -2(1)+8=2 | | 4t^2-40+25=0 | | 0.2x=2.6x-2.8 | | Y=1/3(90-X)-6 | | Y=24-X/3 | | 10-4(3x+1)-(3x-4)= | | 6y-2x=1x | | 5-8x-2x=25 | | 2/7×-7 | | 1(1)-3(-2)+(-2)(-2)= | | 2/3(n-5/6)=5/2 | | 7/10=1/5x | | a1/3 | | 7/9(x-3/7)=7/3 | | 7/9*2 | | x+(x+18)= | | -3(2-9)-4(6-1)= | | 10x-2(x-8)=14whatisx | | 4(5*7)=5(4*7) | | 9(x-3)=8(3+x) | | -3x+1+9x=2(3x-2) | | -13+5x=-73 | | 5x+2(3x+8)+4= | | -7(x-3)-(-3x-9)=-5x | | x/11/x^2/22 | | X=1/3(90-X)-6 | | 6a+4+a+4a= |

Equations solver categories